Glucagon-like peptide-1 receptor expression after myocardial infarction: Imaging study using [68Ga]NODAGA-exendin-4 positron emission tomography - Mia Ståhle; Ville Kytö; Max Kiugel; Heidi Liljenbäck; Olli Metsälä; Meeri Käkelä; Xiang-Guo Li; Vesa Oikonen; Pekka Saukko; Pirjo Nuutila; Juhani Knuuti; Anne Roivainen; et al. (Springer, 2022)
BACKGROUND:
Activation of glucagon-like peptide-1 receptor (GLP-1R) signaling protects against cardiac dysfunction and remodeling after myocardial infarction (MI). The aim of the study was to evaluate 68Ga-NODAGA-exendin-4 positron emission tomography (PET) for assessment of GLP-1R expression after MI in rats.
METHODS AND RESULTS:
Rats were studied at 3 days, 1 and 12 weeks after permanent coronary ligation or a sham-operation. Rats were injected with 68Ga-NODAGA-exendin-4 and scanned with PET and contrast-enhanced computed tomography (CT) followed by digital autoradiography and histology of left ventricle tissue sections. 68Ga-NODAGA-exendin-4 PET/CT showed focally increased tracer uptake in the infarcted regions peaking at 3 days and continuing at 1 week after MI. Pre-treatment with an unlabeled exendin-4 peptide significantly reduced 68Ga-NODAGA-exendin-4 uptake. By autoradiography, 68Ga-NODAGA-exendin-4 uptake was 8.6-fold higher in the infarcted region and slightly increased also in the remote, non-infarcted myocardium at 1 week and 12 weeks post-MI compared with sham. Uptake of 68Ga-NODAGA-exendin-4 correlated with the amount of CD68-positive macrophages in the infarcted area and alpha-smooth muscle actin staining in the remote myocardium.
CONCLUSIONS:
68Ga-NODAGA-exendin-4 PET detects up-regulation of cardiac GLP-1R expression during healing of MI in rats and may provide information on the activated repair mechanisms after ischemic myocardial injury.